The Lu–Hf isotope composition of zircon from syenites of the Saharjok alkaline massif, Kola Peninsula - Vetrin, V. R.; Belousova, E. A. (Geology of Ore Deposits, 2020)
Abstract: Zircon crystals from the alkaline and nepheline syenites of the Saharjok massif, which were formed during the magmatic (2645 ± 7 Ma), hydrothermal (1832 ± 7 Ma), and metamorphic (1784 ± 22 Ma) crystallization stages, were studied. Zircon from alkaline syenites displays lower εHf and εNd values than zircon from ocean island basalts (OIB); these values indicate their affinity to mantle-derived protoliths, which are similar to CHUR in isotope composition. It is assumed that the Neoarchean Keivy alkaline province formed as a result of the plume–lithosphere interaction, induced by the upwelling of a Neoarchean plume, which facilitated metasomatic alteration and the subsequent partial melting of rocks of the subcratonic lithospheric mantle and the crust. The parental melts of the Saharjok massif could have been formed during the resumption of plume activity 20–30 million years after alkaline granite emplacement in the province by the selective melting of the metasomatized lithospheric mantle rocks.